Prophecy as Arguing with God and the Ideal of Justice - Kimelman, Reuven (2014)
Biblical prophecy seeks both to reconcile people to God and to reconcile God with people. Close examination of the roles of Abraham (Genesis 18), Moses (Exodus 32) and Elijah (1 Kings 19) demonstrates that prophets must always bear this dual responsibility, especially in arguing with God, lest they be unworthy of their loyalty both to the people and to God.
Keywords: 1 Kings 19; Exodus 32; Genesis 18; Argumentative prayer; Elijah; Moses; Abraham; Righteousness; Justice; Prophecy